Interactive Translation vs. Pre-Translation in TMs: A Pilot Study - Wallis, Julian (Meta, 2008)
AbstractTranslation clients today are looking for high productivity and quality, but are looking for these at reduced costs. Translation Memory (TM) systems are currently among the most popular translation tools on the market and are intended to help translators produce more translations in a short time period while maintaining high quality and consistency in their work. There are two ways of working with a TM system: interactive mode and pre-translation mode. However, there have been no studies to date which attempt to determine whether one mode is superior to the other. This paper describes a pilot study which investigates which of the two produces better results in terms of productivity, quality and translator satisfaction.